Millennial tourism. An approach to the influence of Instagram advertising for a digital tourism - Centenero de Arce, Maria José (2022)
Nowadays, tourism, in the so-called millennial generation, has shifted from the experience itself and the pleasure of traveling to the pleasure of sharing and finding, in the stories and images narrated in social networks, a way to express their concerns to the world. That is, before embarking on the trip, millennial tourists seek the experience of the chosen place in images that their referents (influencers or prescribers) show in different social networks; in this way they program the mental representations with which they build their trip, and reaffirm from their own testimony or experience. This paper explores some significant examples of how the intersection between tourism promotion and Instagram -as an eminently visual social platform- offers. Starting from a qualitative methodology, the theoretical bases of tourism and the tourist image are reviewed to place them in the current context of the Instagram social network, subjecting these assumptions to analysis through the survey technique, which is applied to millennial tourists, followers of microinfluencers chosen for their relevance in the study. The results of the work show the effects of the influencer on the follower and potential tourist; moreover, in most cases, millennial tourists use the visual suggestions of the posts of their prescribers to discover new tourist destinations.